(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
The Early Cretaceous coral genus Felixigyra Prever, 1909 is revised on the basis of type material from Italy. Felixigyra has a hydnophoroid-meandroid colony organisation with conical monticules attached to each other. The very thick monticules are arranged in a way that calicular centres become apparent. The septa are compact and rhopaloid. The genus can be related to other genera of the Eugyridae family, but differs from them by its particularly developed monticules. It also shows certain resemblance to meandroid genera of the Trochoidomeandridae family. Of the six species originally assigned to Felixigyra only five are recognized, since the type of Felixigyra crassa is too poorly preserved to give a diagnosis. The remaining five species have almost no significant difference in calicular dimensions. In addition to the Italian material, one sample from the Early Cenomanian of Greece and one sample from the Early Albian of Mexico are also assigned to the genus. Material assigned to Felixigyra after Prever (1909) needs to be entirely reclassified to the genus Eohydnophora.